1997
DOI: 10.1002/(sici)1097-4636(199707)36:1<109::aid-jbm13>3.3.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

The influence of alkali and alkaline earths on the working range for bioactive glasses

Abstract: Viscosity-temperature dependence has been investigated for glasses in a system where bioactive compositions are found. A glass is called bioactive when living bone can bond to it. In this work, high-temperature microscopy was used to determine viscosity-temperature behavior for 40 glasses in the system Na 2 O-K 2 O-MgO-CaO-B 2 O 3 -P 2 O 5 -SiO 2 . The silica content in the glasses was 39-70 wt %. All glasses containing <54 mol % SiO 2 devitrified during the viscosity measurements. Generally, glasses that devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
5

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 10 publications
2
54
0
5
Order By: Relevance
“…This is in agreement with previous studies which showed that B 2 O 3 can be used to decrease the T g and forming temperatures of glasses [42]. However, it is interesting to note that the glasses B25 and B100 clearly show two crystallization peaks while S53P4 and B75 only exhibit one crystallization peak.…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with previous studies which showed that B 2 O 3 can be used to decrease the T g and forming temperatures of glasses [42]. However, it is interesting to note that the glasses B25 and B100 clearly show two crystallization peaks while S53P4 and B75 only exhibit one crystallization peak.…”
Section: Discussionsupporting
confidence: 92%
“…Properties such as T g and T c are also critical for the engineering of bioactive glasses with a large window between T g and T c essential in ensuring that the glasses sinter well without crystallisation. The experimental decrease in T g and increase in T c with magnesium substitution resulting in a large sintering window, also noted by Brink et al [18] is again extremely beneficial with respect to bioactive glass design for biological implants.…”
Section: Physical Propertiessupporting
confidence: 63%
“…Magnesia has often been incorporated into bioactive glasses [18][19][20][21][22][23][24][25][26][27][28][29] It is suggested that the lack of structural understanding of magnesium within glasses has lead to the many conflicting views on its contribution with respect to bioactivity. MgO has been documented as decreasing apatite formation in SBF [26] but also, on the other hand, improving the early stages of mineralization [24] and contributing to an intimate contact with living tissue.…”
Section: Introductionmentioning
confidence: 99%
“…31 P MAS NMR is commonly used to study the phosphorus environment (i.e., the proportion of different QP n species) of phospho--silicate bioactive glasses (32) , while 19 F MAS NMR has successfully been used to investigate the structure of fluoride--containing bioactive glasses (14) . Other nuclei used in the characterisation of bioactive glass structure include 23 Na (14,33) , 7 Li (34) and 43 Ca (35) Experimental static 31 P NMR spectra and static spectra obtained from CMD simulations show a similar disagreement: no signal for Q 1 P groups, indicating Si--O--P bonds can be distinguished in experimental spectra in contrast to theoretical spectra. Experimental and theoretical results taken together suggest absence of Si--O--P bonds in Bioglass 45S5, indicating that all phosphorus is present as isolated orthophosphate groups (data taken from (37) with permission, © American Chemical Society).…”
Section: Techniquesmentioning
confidence: 99%
“…Bioactive glasses are typically multicomponent systems, often containing two network formers (SiO2 and smaller amounts of P2O5 (8) ) besides large concentrations of various network modifiers (CaO and Na2O mostly, but also SrO (22) , K2O (23) , MgO (24) or Li2O (25) ) as well as other components such as fluorides (26) or chlorides (27) , making the occurrence of heterogeneities at a nano--scale more likely. Heterogeneities are understood to be important factors in effects such as phase separation, nucleation and crystallisation (28) or density and rigidity (29) in glasses, but are also likely to affect degradation and ion release (30) .…”
Section: Introductionmentioning
confidence: 99%